Web 2.0—The past and the future. Issue 4 (August 2016) - Newman, Russell; Chang, Victor; Walters, Robert John; Wills, Gary Brian
Highlights: We provide review of Web 2.0 including its past and future perspectives. We present Web 3.0 with its desired features. We have inspected the development of Web 2.0/3.0 between year 2005 and 2016. Abstract: Although it has been around for 11 years, it is still not clear where Web 2.0 will lead. This paper presents a general discussion of past and recent trends that may positively influence the direction of Web 2.0, including cloud computing and other emerging business models. In order to move forward, Web 3.0 is proposed for the next generation of work that integrates Cloud Computing, Big Data, Internet of Things and security. We also present criteria and future direction for Web 3.0 to allow all services and people can stay connected with each other.